Religion, music, community the interferences of the Pentecostal charismatic renewal and the Catholic charismatic renewal - Povedák Kinga (Religion, culture, society, 2014)
In the article the author focuses on the Pentecostal-Charismatic Renewal movements that attract rapidly increasing number of followers all over the world and in recent years in Hungary as well. She intends to show how this fundamentally Protestant-inspired trend appears within Catholic frameworks and look at the demands and cultural processes behind the syncretising phenomenon. The blurring of boundaries and the transposable patterns are clearly reflected in the common use of the worship-song repertoire.